Understanding Consumers' Purchase Intention and Gift-Giving in Live Streaming Commerce: Findings from SEM and fsQCA - Wen-Kuo Chen; Chien-Wen Chen; Andri Dayarana K. Silalahi (Emerging Science Journal, 2022)
Live streaming commerce has experienced tremendous growth over the past few years. Although research has increasingly investigated the phenomenon of live streaming as e-commerce, it is arguably essential to determine why consumers make purchases through live streaming and send paid gifts to streamers. This study aims to understand users' social commerce purchase intentions and gift-giving according to the uses and gratification perspective, and engagement, and extends the literature by identifying five uses and gratifications for social media live streaming and how the viewers' engagement affects purchase intentions and gift-giving. We tested the hypothesis among 525 Indonesians who watch live streaming through Structural Equation Modeling (SEM) and fuzzy set Qualitative Comparative Analysis (fsQCA). The results of SEM confirm the importance of pass-times and habits to consumer engagement in live streaming. In this sequence, the role of engagement (emotional, social presence, and immersion) was confirmed to significantly influence purchase intention and gift-giving intention. The results of fsQCA provide theoretical insight and practical suggestions for increasing our understanding of the complex interconnectivity among uses, gratification factors, engagement in social commerce purchase intentions, and gift-giving intentions. Finally, this study also highlighted the configurational conditions for understanding consumer behaviors in live streaming commerce. Doi: 10.28991/ESJ-2022-06-03-03 Full Text: PDF